Alanis Obomsawin: The Vision of a Native Filmmaker - Lewis, Randolph (University of Nebraska Press, 2006)
In more than twenty powerful films, Abenaki filmmaker Alanis Obomsawin has waged a brilliant battle against the ignorance and stereotypes that Native Americans have long endured in cinema and television. In this book, the first devoted to any Native filmmaker, Obomsawin receives her due as the central figure in the development of indigenous media in North America.